When Do Capital Inflow Surges End in Tears? - Ghosh, Atish R.; Ostry, Jonathan D.; Qureshi, Mahvash S. (American Economic Review, 2016)
We investigate in a sample of 53 emerging markets over 1980-2014 whether countries with open capital accounts are necessarily at the mercy of global events, or are able to take policy actions when receiving inflows to mitigate the impact of a subsequent reversal. Our analysis suggests that, while changes in global conditions have an important bearing on crisis susceptibility, countries that allow the buildup of macroeconomic and financial vulnerabilities during boom times, and which receive mostly debt flows, are significantly more likely to see capital inflow surge episodes end in a financial crisis.